A Case Study of Socioeconomic Inequalities of Young Agricultural Migrant Workers in District Kewra, Haryana - Tokas, Ms. Manurut; Chauhan, Dr. Tarun (The journal of contemporary issues in business and government, 2022)
Rural-to-urban migration is an ongoing process under the current circumstances. 54% of the world's population lives in urban areas and has access to per capita employment resources. India and Nigeria have the highest growth rates, according to a United Nations report. This study is being conducted with the aim of analyzing the access to health care of the migrant population in Kewra Village, Haryana. Interstate immigrants are coming to Haryana and other metropolitan areas of India in hopes of a better quality of life, higher incomes, better education and better health facilities. But the harsh reality is that these development indicators are not readily available to the majority of the immigration-dependent Indian population. In Haryana, migrant workers are generally absorbed into the agricultural sector. These migrant workers are forced to work on the land of other farmers and landlords. They only contribute to the production of agricultural products and do not own any land within the state for their own consumption or farming. Some of these migrant workers tend to work in the same fields for long periods of time, earning a daily wage as a reward for their loyalty, but some are also promoted to share in the harvest. These migrant workers are an important source of capital and contribute significantly to the production of landlords and farmers.